The Effectiveness of Influencer Marketing in Digital Campaigns for Beauty Products - Fahad Khan Afridi; Hidayat, Agus Rohmat (Politeknik Siber Cerdika Internasional, 2024)
In recent years, influencer marketing has emerged as a powerful component in digital advertising strategies, particularly in the beauty industry. The proliferation of social media platforms such as Instagram, YouTube, and TikTok has enabled beauty influencers to build large followings and significantly shape consumer preferences and purchase decisions. This paper investigates the effectiveness of influencer marketing in digital campaigns for beauty products by exploring how influencer credibility, content quality, audience engagement, and brand alignment contribute to campaign success. Through a qualitative approach and literature review, the study identifies key factors influencing campaign effectiveness and highlights both opportunities and challenges for marketers. Findings indicate that influencer marketing can enhance brand awareness, drive consumer trust, and increase sales conversions when executed with strategic precision. However, issues such as influencer authenticity, audience skepticism, and algorithmic changes may affect outcomes. The paper concludes by offering strategic recommendations for brands aiming to leverage influencer marketing to achieve measurable results in the highly competitive beauty sector.